The influence of conflict in group work according to Tuckman’s Model / Wan Syariza Wan Yadri … [et al.] - Wan Yadri, Wan Syariza; Ahmad, Nur Haziq Fikri; Abdul Kadar, Nur Syafiqah; Nazym, Nur Kairanbayeva; Mohd Johari, Muhammad Danish (Universiti Teknologi Mara Cawangan Pulau Pinang, 2024)
This study explores the perspectives of foundation studies students in Malaysia regarding the four stages of the Tuckman Model (forming, storming, norming, performing) in the context of group work. Additionally, it examines the correlation between these phases and conflicts within a group. The study, which involved 178 individuals, reveals significant links between different stages of group growth that influence both group dynamics and learning outcomes. The findings highlight the significance of competent leadership in handling the storming phase and emphasise the critical roles of communication and trust in the shaping and norming stages. Furthermore, the results emphasise the importance of connectedness in improving group productivity throughout the performing phase. Proficiently managing disagreements has been demonstrated to improve group dynamics and promote development. This study offers crucial insights into the ways in which organised group interactions might enhance educational settings by analysing both the difficulties and favourable aspects of each phase. Suggestions encompass techniques for enhancing communication and collaboration abilities, along with guidance for maximising teaching approaches by gaining a more profound comprehension of group dynamics.